EFFECTINENESS WORKER OF PASSPORT DEPARTMENT, DEPARTMENT OF CONSULAR AFFAIRS, MINISTRY OF FOREIGN AFFAIRS SRINAKARIN PASSPORT OFFICE - ดำทองสุก วิชญาภา (Pathumthani University Academic Journal, 2022)
The objectives of this research were to study: 1) study the level of effectiveness in the operation of the Passport Department 2) to study level of motivation for work and 3) to study the operational motivations affecting the efficiency of the Passport Department’s performance. Srinakarin Passport Office, Department of Consular Affairs, Ministry of Foreign Affairs It is mixed research. The target population is passport officer Srinakarin Passport Office, Department of Consular Affairs, Ministry of Foreign Affairs, total of 85 people. The sample consisted of 70 passport officers, which the researcher used to calculate the sample size using the Crazy and Morgan formula. The interviewees were 1 division director, 1 department head, and 3 deputy chiefs, totaling 5 persons. The mean value of each question (IOC) was .80-1.00 and the confidence value was .87. Statistics in the research included percentage, mean, standard deviation and multiple regression analysis. The research results revealed that: 1 Motivation for Operation of the Passport Department, Department of Consular Affairs, Ministry of Foreign Affairs Srinakarin Passport Office Overall, it was at a high level in all aspects. When considering each aspect, it was found that the relationship between colleagues with the highest average, followed by policy and administration; 2) Performance efficiency of the Passport Department, Department of Consular Affairs, Ministry of Foreign Affairs. Srinakarin Passport Office Overall, all aspects were at a high level. 3) The relationship between performance motivation affecting the efficiency of passport department. Srinakarin Passport Office, Department of Consular Affairs, Ministry of Foreign Affairs found that the adequacy of compensation and welfare and command control There was a statistically significant positive correlation with work efficiency at the .01 level.